Family violence and nursing practice - Humphreys, Janice; Campbell, Jacquelyn (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2004)
Domestic violence presents significant assessment and treatment challenges for today's nurses. This landmark resource -- written by two of the foremost experts in the field -- provides uniquely comprehensive, nursing-focused coverage of family violence, offering both practicing nurses and nursing students a clear view of the essential theories, interventions, and issues. Complete and timely coverage addresses the topics most relevant to nursing practice -- including theories of aggression and family violence, violence against female partners, abuse against pregnant women, child abuse, elder abuse, sexual abuse, adolescent dating violence, and children of battered women.
Theoretical background. Theories of aggression and family violence -- Theories of intimate partner violence -- Theories of child abuse. Nursing practice. Abuse during pregnancy -- Abuse and neglect of the elderly in family settings -- Children of abused women -- Sexual abuse in families -- Nursing care of families using violence -- Nursing care of abused children -- Nursing care and adolescent dating violence -- Nursing care of survivors of intimate partner violence -- Nursing care of abused women with disabilities. Nursing education, policy, and future. Legal and forensic nursing responses to family violence -- Future directions.
Includes index.
Keywords: VICTIMS OF FAMILY VIOLENCE -- MEDICAL CARE